(untitled) (Global Journal of Human-Social Science, 2016)
Disability sports have acquired an indispensable status in the life of many nations and the special athlete as a whole. Special athletes are exposed to a number of intense physical and psychosocial demand and they needed to make use of a set of cognitive and behavioural strategies in order to cope with these challenges and related fatigue. Hitherto, previous studies had focused largely on adaptive sports and effects of sporting activities on persons with disability without establishing a link between disabled athlete’s use of coping strategies and their achievement motivation. Therefore, it is on this premise that this study harps on the relationship between fatigue indices and coping strategies among Oyo State special athletes. Descriptive survey design using purposive sampling technique was employed. Participants of the study include all the registered special athletes in Oyo State comprising of one hundred and twenty three (123) athletes. Two standardized instruments, thus, Modified fatigue impact scale (r=0.384) and Athletic coping skills inventory (r=0.514) were both employed.